1963
DOI: 10.1071/bi9630717
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Gluten Fractions Prepared by Ion-Exchange Chromatography on Carboxymethyl-Cellulose

Abstract: SummarySeven fractions obtained from wheat gluten by chromatography on carboxy~ methyl-cellulose were studied by ultracentrifugation, gel electrophoresis, chemical, and N-terminal amino acid analysis. On rechromatography, five fractions eluted by sodium chloride behaved as distinct entities. illtracentrifuge experiments indicated that four of these were each undergoing rapid, reversible association. Several N-terminal amino acids were found in each of the fractions which, moreover, could be resolved by the gel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1965
1965
1966
1966

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…. Gel electrophoretic patterns of fractions resulting from the carboxymethyl cellulose (CMC) fractionation of Simmonds and Winzor (1961) have been published by Graham (1963) and by Lee et al (1963). These results showed that each fraction was heterogeneous, with considerable overlapping of electrophoretic bands from neighbouring fractions, and that fractions eluted late in the chromatogram were contaminated because of tailing of earlier fractions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…. Gel electrophoretic patterns of fractions resulting from the carboxymethyl cellulose (CMC) fractionation of Simmonds and Winzor (1961) have been published by Graham (1963) and by Lee et al (1963). These results showed that each fraction was heterogeneous, with considerable overlapping of electrophoretic bands from neighbouring fractions, and that fractions eluted late in the chromatogram were contaminated because of tailing of earlier fractions.…”
mentioning
confidence: 99%
“…Gluten proteins were extracted from Gabo flour as described previously (Coates and Simmonds 1961;Lee et al 1963). Columns (1•5 by 25 cm) containing about 3 g CMC (Whatman CM70 powder) were maintained at 40°C and were eluted at 1 ml/min; fractions were collected at lO-min intervals.…”
mentioning
confidence: 99%